Comparative analysis of spatial architectures and cellular proportions in Lung, Breast, and Intestinal tissues recovered by different mapping tools. - Huamei Li (8815955) (2025)
(A–D) Spatial architectures of human Lung (A), Breast (B and C), and Intestinal (D) tissues reconstructed by Cell2Spatial, CytoSPACE, CellTrek, Tangram, and Seurat. Each dot represents an individual cell and cell types are marked by color codes. (E–H) Scatter plots showing the consistency between the cellular proportions in spatial architectures reconstructed with various mapping tools and the cellular compositions predicted by CARD spatial deconvolution tool [11]. The blue line denotes the linear fit, and the shaded area represents the 95% confidence interval. Different colors of points indicate distinct cell types. “R” represents the Pearson correlation coefficient (PCC). P-values were obtained by two-sided t-tests. (E) Lung; (F) BRCA.1; (G) BRCA.2; (H) Intestinal. (I) Table summarizing the number of cell types effectively mapped to spatial locations by each tool. “Reference” represents the total number of cell types in the single-cell atlas of the human tissues. The underlying data for this figure can be found at https://zenodo.org/records/17212677. (TIF)